2015
DOI: 10.1093/mnrasl/slu195
|View full text |Cite
|
Sign up to set email alerts
|

A NuSTAR observation of the fast symbiotic nova V745 Sco in outburst

Abstract: The fast recurrent nova V745 Sco was observed in the 3-79 keV X-rays band with NuSTAR 10 days after the optical discovery. The measured X-ray emission is consistent with a collisionally ionized optically thin plasma at temperature of about 2.7 keV. A prominent iron line observed at 6.7 keV does not require enhanced iron in the ejecta. We attribute the X-ray flux to shocked circumstellar material. No X-ray emission was observed at energies above 20 keV, and the flux in the 3-20 keV range was about 1.6 × 10 −11 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 28 publications
2
51
0
Order By: Relevance
“…Interestingly, our N H values are quite similar to those measured for 2 recurrent novae known to have red giant companions: V745 Sco and RS Oph. In RS Oph, the values for N H were ∼ 10 23 cm −2 just 0.16 days after eruption, but fell to ∼ 10 22 cm −2 by Day 3.23 and were ∼ 8 × 10 21 cm −2 by Day 10 (Orio et al 2015). In RS Oph, Nelson et al (2008) reported N H ∼ 10 22 cm −2 14 days after eruption.…”
Section: X-raysmentioning
confidence: 97%
“…Interestingly, our N H values are quite similar to those measured for 2 recurrent novae known to have red giant companions: V745 Sco and RS Oph. In RS Oph, the values for N H were ∼ 10 23 cm −2 just 0.16 days after eruption, but fell to ∼ 10 22 cm −2 by Day 3.23 and were ∼ 8 × 10 21 cm −2 by Day 10 (Orio et al 2015). In RS Oph, Nelson et al (2008) reported N H ∼ 10 22 cm −2 14 days after eruption.…”
Section: X-raysmentioning
confidence: 97%
“…Model parameter estimation was undertaken using the XSPEC fitting engine, applying isothermal APEC models attenuated by a variable absorption component representing the circumstellar environment combined with a fixed interstellar absorption corresponding to a neutral hydrogen column density of 5.6 × 10 21 cm −2 . A metallicity of 0.51 times the solar abundances of Anders & Grevesse (1989) was adopted, following Orio et al (2015). Unfortunately, during the SSS phase there was insufficient signal at higher energies above that of the SSS signal with which to constrain the plasma temperature; consequently, there is a gap in the Swift temperatures between days 4 and 12.…”
Section: Swift Xrt Observationsmentioning
confidence: 99%
“…The explosion triggered observing campaigns over the entire electromagnetic spectrum, including radio (Rupen et al 2014;Kantharia et al 2016), infrared (Banerjee et al 2014), optical (Anupama et al 2014;Mróz et al 2014), X-ray Drake et al 2014;Mukai et al 2014;Page et al 2015), hard X-ray (Rana et al 2014;Orio et al 2015), and γ-ray (Cheung et al 2014(Cheung et al , 2015 wavelengths. Page et al (2015) present a detailed summary of the various observations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, at least 14 Galactic novae (including three confirmed and one suspected RN) have been observed with a decline time  t 4 2 days (see Hounsell et al 2010;Strope et al 2010;Munari et al 2011;Orio et al 2015), and these are summarized in Table 5. M31N 2008-12a resides at the faster end of this rapidly declining sample, exhibiting decline times very similar to those of the RN USco (marginally slower to t 2 but faster to t 3 , assuming V-band luminosities), and exhibits the only known decline with < t 3 3 days.…”
Section: Initial Decline (Day 1-4)mentioning
confidence: 99%